The Main Ideas of Mieczysław Wallis’ Program of Philosophical Anthropology - Zegzuła-Nowak, Joanna (Filozofia Nauki, 2022)
The article presents the results of several years of analytical and reconstruction efforts carried out by the author who focused on archival writings by Mieczysław Wallis, a representative of the second generation of the Lvov-Warsaw School, which were to a large extent unknown to readers. Wallis’ intellectual profile has been associated so far mostly with his writings on art criticism, aesthetics, theory, and history of art. In the light of painstaking, multistage research of the large collection of his unpublished archival works, it turned out that the current perception of his intellectual preferences and academic achievements is too narrow and simplified. What is especially little known and insufficiently edited are his notes on philosophical anthropology, discussing the question of human existence and human activity in the world. They contain a unique philosophical program based on the axiological concept called psychological relationism. Its main category is the “homo creativus” approach. Wallis’ intellectual program is a valuable contribution to the achievements of the Lvov-Warsaw School and, in general, to the Polish philosophy of the 20th century.